Nama Jurus Silat di Perguruan Cacag Lembang sebagai Refleksi Karakteristik Masyarakat Betawi - Kurniasih, Wida; Widiatmoko, Sigit (Risenologi, 2023)
The characteristics of the Betawi people cannot only be seen from their behavior, but can be found in many ways. Generally, people will instill their character in important things that can indicate their identity. Example, such as pouring it into the distinctive culture of the community itself, one thing that can be seen is pencak silat. The purpose of this research is to describe the meaning of the Betawi martial arts moves and reveal the reflection of the characteristics of the Betawi people in the name of the martial arts moves at the Cacag Lembang college. The method used in this study is a qualitative descriptive research method with an anthropolinguistic approach. The data or corpus in this study are the names of the martial arts moves at the Cacag Lembang Silat College which includes the names of all the moves, their meanings, and the origins of their names. Data was taken directly through observation by observing when there were routine exercises and interviews with the head of the college. Analysis begins with searching data through the process of field notes, documentation, and interviews. Data found is arranged systematically by organizing the data in a category, describing it in units, synthesizing it, rearranging it in a pattern, selecting important data, and ending with drawing conclusions. The results of the study from 20 naming data, there are 6 characteristic reflections that are reflected in the naming of the martial arts, belief in religion, peace-loving, tough and principled, spontaneous, hardworking, and brave.